Perancangan Media Pembelajaran Interaktif Berbasis Model Pembelajaran Problem Based Learning Mata Kuliah Fisika Dasar - Syahputra, Andrian; Suparno, Suparno; Giatman, Muhammad; Maulida, Rizki (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
This study aims to design a learning media based on the Problem Based Learning (PBL) learning model. This research is included in R&D (Research and Development) research, which is research that produces products that can be used to support the learning process of basic physics courses at Potensi Utama University. Making learning media using flash multimedia. The design of instructional media is made by IT practitioners, namely lecturers in the field of computers. Furthermore, to assess the suitability of the material of this study using a team of experts from several basic physics lecturers and physics teachers. The results of this study are the design of PBL-based learning media is quite feasible and in accordance with the physics material, especially HK. Newton. The assessment of the material suitability by the expert team is the feasibility of the content / depth of university level material with a percentage value of 82.85%. Contextual percentage of 81.20%. Presentation Feasibility 80.15%. Conformity to the model. PBL 86.25%. Suitability of evaluation with learning objectives 87.10%.